OPTIMALISASI STRATEGI PEMASARAN LEMBAGA BIMBINGAN BELAJAR BAHASA INGGRIS MENGGUNAKAN METODE EDUCATION SERVICE QUALITY - Wibawa, Berto Mulia; Aryanto, Muhammad Fadillah (Jurnal Manajemen, 2016)
The importance of the needs of excellent English Language competence in this globalization era makes people always look for credible english course institutions which provide excellent quality of service that will lead to excellent rate of customer satisfaction. Education service quality is a modification of service quality model which related to service industry in the field of education, including english course institution. This research aims to analyze the influence of education service quality to the customer satisfaction and loyalty. Methods of this research used descriptive analysis, confirmatory factor analysis, and regression analysis. The result of this research showed that from the three latent variables of education service quality (requisite, acceptable, and functional), only requisite and functional which are known to have positive significant influence to the customer satisfaction. Furthermore, customer satisfaction is significantly influenced to the customer loyalty.